Quantifying training and game demands of a National Basketball Association season - Russell, J. L.; McLean, B. D.; Stolp, S.; Strack, D.; Coutts, A. J. (Frontiers in Psychology, 2021)
Purpose: There are currently no data describing combined practice and game load demands throughout a National Basketball Association (NBA) season. The primary objective of this study was to integrate external load data garnered from all on-court activity throughout an NBA season, according to different activity and player characteristics.